Emerging diseases of sugarcane and new disease management strategies - Viswanathan, Rasappa (Journal of Sugarcane Research, 2023)
In India, sugarcane is affected by various diseases caused by fungi, bacteria, viruses and phytoplasmas. Favourable environment for the crop growth also favours build-up of diseases and many disease epidemics have caused serious crop losses in different states. Severe epidemics of red rot, smut and wilt have resulted in withdrawal of several elite varieties from cultivation. Apart from these diseases, several other diseases once considered as ’minor diseases’ gained momentum in the recent decades and became serious threat to sugarcane cultivation in India. Increased severities of twisted top (Pokkah boeng), brown rust and brown spot were reported from different states. These diseases must be tackled immediately either by withdrawing the affected varieties or taking up appropriate disease management measures. Virus diseases occur throughout sugarcane growing states with severe crop losses due to ignorance about the disease or wrong perception that they do not cause serious damage to sugarcane. In addition, varietal degeneration caused by the non-fungal diseases has been a major threat to cane cultivation in the country. Hence, healthy seed cane nurseries based on meristem culture combined with molecular diagnosis became more relevant to rejuvenate the elite varieties affected by varietal degeneration. The review focuses on emerging diseases that pose challenges to cane cultivation in India and overall disease management strategies to be adopted to successfully manage the diseases.